Applications of Variational Method to Impulsive Fractional Differential Equations with Two Control Parameters (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the existence of the impulsive fractional differential equation. Based on a previous paper [2], we give more accurate condition to guarantee the impulsive fractional differential equation has at least three solutions under certain assumptions by using variational methods and critical point theory. Moreover, some recent results are generalized and significantly improved.
Keywords: Impulsive fractional differential equations; Variational methods; Critical point theory; Three solutions.